The Current Debate on the Relationship between Sin and Sickness in John 5:14 - Kubiś, Adam (The Biblical Annals, 2022)
The article focuses on the understanding of sin in John 5:14, as well as the relationship between sin and sickness presented in this verse. It provides a thorough status quaestionis on both of these issues. After examining various hypotheses regarding the meaning of sin in John 5:14, the Johannine notion of sin as unbelief is expounded as the most convincing. This sin encompasses the past, present, and future life of the healed man. Thus, contrary to the exegetical opinio communis, the cause-and-effect relationship between sin and sickness does not apply to John 5:14. In light of this explanation, the messages of John 5:14 and 9:2–3 do not contradict each other. Jesus’ words in 5:14, intentionally pronounced in the temple, should be understood as an invitation to follow him in faith.